2012
DOI: 10.1111/jfpp.12041
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Extrusion Conditions on the Physicochemical Properties and Sensory Characteristics of Fish-Based Expanded Snacks

Abstract: Expanded products with fish flour, rice and corn flour was prepared using a twin‐screw extruder with varying temperature, screw speed, total moisture and fish flour content to establish their effect on the expansion ratio, bulk density, porosity and water solubility index of the extrudates adopting response surface methodology. The experiments were optimized using five‐level, four‐factor central composite design. Analysis of variance was carried to study the effects of main factors and interaction effects of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 46 publications
3
17
0
2
Order By: Relevance
“…High screw rate causes sufficient mixing, increase in the chain splitting of starch, which increased the number of nucleation sites in the die; therefore, increase bubble growth and expansion (Altan et al, ). Similar observations of the effect of screw rate on the product expansion were reported for barley grits‐barley flour, crab‐corn flour, fish flour‐rice, and corn flour (Altan et al, ; Majumdar & Singh, ; Obatolu, Skonberg, Camire, & Dougherty, ). Obatolu et al () showed that the expansion ratio was improved by increasing the screw rate at constant moisture content for extruded crab based snacks.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…High screw rate causes sufficient mixing, increase in the chain splitting of starch, which increased the number of nucleation sites in the die; therefore, increase bubble growth and expansion (Altan et al, ). Similar observations of the effect of screw rate on the product expansion were reported for barley grits‐barley flour, crab‐corn flour, fish flour‐rice, and corn flour (Altan et al, ; Majumdar & Singh, ; Obatolu, Skonberg, Camire, & Dougherty, ). Obatolu et al () showed that the expansion ratio was improved by increasing the screw rate at constant moisture content for extruded crab based snacks.…”
Section: Resultssupporting
confidence: 74%
“…. Similar observations of the effect of screw rate on the product expansion were reported for barley gritsbarley flour, crab-corn flour, fish flour-rice, and corn flour(Altan et al, 2009;Majumdar & Singh, 2014;Obatolu, Skonberg, Camire, & Dougherty, 2005) Obatolu et al (2005). showed that the expansion ratio was improved by increasing the screw rate at constant moisture content for extruded crab based snacks.…”
supporting
confidence: 77%
“…We found that VCO cake levels >30% and feed moisture >18% were unsuitable because they had high bulk density and less expansion ratio. Similarly, Majumdar and Singh (2014) and Pardhi, Singh, Nayik, and Dar (2016) found that feed moisture of 14-18% was suitable for production of fish flour and brown rice grits based extrudates, respectively. The extrudates obtained at 300-350 rpm screw speed had the best properties.…”
Section: Preliminary Studiesmentioning
confidence: 94%
“…However, health concerns cause many consumers to reduce the consumption of extruded snacks in their diets because many of these products contain 25% oil which contains saturated fatty acids and also a high content of trans fatty acids. On the other hand, their major ingredients are cereals which contain low protein and essential amino acid contents, particularly lysine (Majumdar & Singh, ).…”
Section: Introductionmentioning
confidence: 99%